Maximal power of the lower limbs of youth gymnasts and biomechanical indicators of the forward handspring vault versus the sports result - Kochanowicz, A.; Kochanowicz, K.; Niespodziúski, B.; Mieszkowski, J.; Aschenbrenner, P.; Bielec, G.; Szark-Eckardt, M. (Journal of Human Kinetics, 2016)
The aim of the study was to define the relationship between maximal power of lower limbs, the biomechanics of the forward handspring vault and the score received during a gymnastics competition. The research involved 42 gymnasts aged 9-11 years competing in the Poland`s Junior Championships. The study consisted of three stages: first -estimating the level of indicators of maximal power of lower limbs tested on a force plate during the countermovement jump; second - estimating the level of biomechanical indicators of the front handspring vault. For both mentioned groups of indicators and the score received by gymnasts during the vault, linear correlation analyses were made. The last stage consisted of conducting multiple regression analysis in order to predict the performance level of the front handspring vault. Results showed a positive correlation (0.401, p < 0.05) of lower limbs` maximal power (1400 ± 502 W) with the judges` score for the front handstand vault (13.38 ± 1.02 points). However, the highest significant (p < 0.001) correlation with the judges` score was revealed in the angle of the hip joint in the second phase of the flight (196.00 ± 16.64°) and the contact time of hands with the vault surface (0.264 ± 0.118 s), where correlation coefficients were: -0.671 and -0.634, respectively. In conclusion, the angles of the hip joint in the second phase of the flight and when the hands touched the vault surface proved to be the most important indicators for the received score.